Effect of Transcranial Direct Current Stimulation on Functional Capacity in Schizophrenia: A Study Protocol for a Randomized Controlled Trial - Narita, Zui; Inagawa, Takuma; Maruo, Kazushi; Sueyoshi, Kazuki; Sumiyoshi, Tomiki (Frontiers in Psychiatry, 2017)
Schizophrenia patients elicit a wide range of psychopathology, including psychotic symptoms, mood symptoms, and cognitive impairment. Functional capacity is defined as the ability to perform everyday living skills, which is linked to cognition and real-world functional outcome. In a previous open trial, we demonstrated that transcranial direct current stimulation, one of the neuromodulation methods, improved cognition and functional capacity in 28 patients with schizophrenia. However, since it was a pilot study, a controlled trial is needed. Therefore, we present a study protocol for a randomized controlled trial designed to evaluate the effect of transcranial direct current stimulation on functional capacity in patients with schizophrenia. This is a two-arm, parallel-design, randomized controlled trial, in which patients and assessors will be blinded. Patients meeting DSM-5 criteria for schizophrenia will be enrolled, and randomized to receive either active- or sham stimulation (with 10 sessions in five consecutive days). Functional capacity will be evaluated by the UCSD Performance-based Skills Assessment-Brief as primary outcome. Cognition, as measured by the Brief Assessment of Cognition in Schizophrenia, and psychotic symptoms, as measured by the Positive and Negative Syndrome Scale will also be evaluated. Data will be collected at baseline, immediately after the last stimulation, and one and two months thereafter. If active stimulation elicits greater effects compared to those of sham stimulation, it may add to the efforts to improve functional outcomes by neuromodulation in patients with schizophrenia.